2008
DOI: 10.3319/tao.2008.19.4.363(images)
|View full text |Cite
|
Sign up to set email alerts
|

Sea Surface Temperature, Productivity, and Terrestrial Flux Variations of the Southeastern South China Sea over the Past 800000 Years (IMAGESMD972142)

Abstract: Variations in sea surface temperature (SST), productivity, and biogenic components such as total organic carbon (TOC), carbonate, and opal contents measured from IMAGES (International Marine Global Changes Study) core MD972142 provide information about long-term paleoceanographic changes during the past~870000 years in the southeastern South China Sea (SCS). MD972142 U 37 k' -SSTs varied from 25 to 29°C, paralleling the glacial to interglacial changes. MD972142 biogenic components show relatively high carbonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
21
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 49 publications
(52 reference statements)
6
21
0
Order By: Relevance
“…For the southeastern SCS, TOC and organic biomarkers indicate higher primary productivity during glacial periods being ascribed to stronger EAWM Shiau et al, 2008). As 5 aforementioned, our model case in glacial condition favors vigorous diapycnal mixing to support paleorecords of increased primary productivity.…”
Section: Productivity-driven Redox Changes and Organic Matter Preservsupporting
confidence: 60%
See 1 more Smart Citation
“…For the southeastern SCS, TOC and organic biomarkers indicate higher primary productivity during glacial periods being ascribed to stronger EAWM Shiau et al, 2008). As 5 aforementioned, our model case in glacial condition favors vigorous diapycnal mixing to support paleorecords of increased primary productivity.…”
Section: Productivity-driven Redox Changes and Organic Matter Preservsupporting
confidence: 60%
“…In fact, Mn content in core MD972142 was determined by XRF (X-ray fluorescence spectrometer) and had been reported by Löwemark et al (2009); however, our ICP-OES provide more 20 quantitative result. Total organic carbon (TOC) reported by , C37 Alkenones by Shiau et al (2008) and planktonic foraminiferal δ 18 O by Wei, K. Y. et al (2003) were drew for discussion.…”
Section: Sample and Chemical Analysismentioning
confidence: 99%
“…The MD972142 results nicely demonstrate that more records using biomarkers as community structure proxies can help resolve some of these questions. Shiau et al (2008) also observed a long-term increased trend in all productivity proxies since the mid-Brunhes. This, coupled with the MD012380 record from the Sulu Sea , suggests a change in the tropical western pacific, probably in response to the increased strength of the East Asian monsoon system.…”
mentioning
confidence: 76%
“…However, it is not clear why the opal content was lower during the glacials. If one assumes that the opal content is purely a proxy for diatom productivity, then the results by Shiau et al (2008) imply that there was a major phytoplankton community structure change for the site during glacial-interglacial cycles. It can be inferred from their data that diatom contribution to total productivity was lower during the glacials when the total productivity was higher, and its contribution was higher during the interglacials when total productivity was lower.…”
mentioning
confidence: 99%
See 1 more Smart Citation